1996
DOI: 10.1074/jbc.271.16.9298
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Function Properties of the Yeast Dual Regulator Protein NGG1 That Are Required for Glucose Repression

Abstract: NGG1p/ADA3p is a yeast dual function regulator required for the complete glucose repression of GAL4p-activated genes (Brandl, C. J., Furlanetto, A. M., Martens, J. A., and Hamilton, K. S. (1993) EMBO J. 12, 5255-5265). Evidence for a direct role for NGG1p in regulating activator function is supported by the finding that NGG1p is also required for transcriptional activation by GAL4p-VPl6 and LexA-GCN4p (Pina, B., Berger, S. L., Marcus, G. A., Silverman, N., Agapite, J., and Guarente, L. (1993) Mol. Cell. Biol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 73 publications
1
43
0
Order By: Relevance
“…Direct interaction in vitro has been observed between ADA2p and both GCN5p and the carboxyl-terminal 250 amino acids of NGG1p (13,16). Based on the finding that single and double disruptions of ngg1 and ada2 have similar effects on inhibition of GAL4p and PDR1p, we suggested that the same or related ADA complexes are involved in transcriptional activation and repression (9,18). Other coactivator complexes also appear to be involved in the positive and negative regulation of transcription.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Direct interaction in vitro has been observed between ADA2p and both GCN5p and the carboxyl-terminal 250 amino acids of NGG1p (13,16). Based on the finding that single and double disruptions of ngg1 and ada2 have similar effects on inhibition of GAL4p and PDR1p, we suggested that the same or related ADA complexes are involved in transcriptional activation and repression (9,18). Other coactivator complexes also appear to be involved in the positive and negative regulation of transcription.…”
mentioning
confidence: 86%
“…CY946 is a derivative of CY914 that contains a Tn10 LUK disruption of the ADA2 coding region (kindly provided by J. Horiuchi and L. Guarente) (10). CY947 and CY1077 are derivatives of CY946 and CY914, respectively, that contain Myc-tagged NGG1 expressed from the DED1 promoter integrated at his3 (18).…”
Section: Yeast Strains Media and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations